Nature of Escherichia coli cell lysis by culture supernatants of Bacillus species. - Dean, C R (1991)
Escherichia coli cells were found to be sensitive to lysis by the supernatants of a variety of protease-positive Bacillus species when treated at 45 degrees C but not when treated at 37 degrees C. Different E. coli strains manifested different lysis sensitivities when treated at 45 degrees C. When the lysis rates of E. coli cells at various stages of growth were investigated, post-exponential-phase cells were shown to be most sensitive to lysis. The lysis rate was inversely related to cell viability, and susceptibility appeared to be at least partly due to lysis of dead E. coli cells. A close relation was observed between levels of lysis activity and proteolytic activity. A Bacillus subtilis mutant lacking alkaline and neutral protease activity failed to lyse E. coli cells. It was concluded that Bacillus proteases played a major role in the observed E. coli lysis.